PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS DI SEKOLAH DASAR - Rosanti; Nurhaswinda; Yanti Yandri Kusuma; Fadhilaturrahmi; Rusdial Marta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the improvement of students' mathematical communication skills in mathematics learning through the problem based learning model in class IV of Muhammadiyah 028 Penyasawan Elementary School. This research is motivated by the low mathematical communication of students. This research is a classroom action research. The subjects in this study were 1 teacher and 20 fourth-grade students of Muhammadiyah 028 Penyasawan Elementary School. The object of this research is the problem based learning model and mathematical communication skills. This research was conducted in 2 cycles, each cycle carried out 2 meetings. The data collection techniques used in this study were tests, observation and documentation. Meanwhile, the data analysis used was descriptive qualitative and quantitative with percentages. Based on the increase in the number of students who achieved the criteria for achieving learning objectives (KKTP) and the increase in class average scores and classical scores. The presentation value of students' mathematical communication skills before the action showed that 6 students or 30% were in the very poor mathematical communication skills category. Then after applying the problem based learning model in cycle I meeting I there were 9 students who achieved mastery, which is 45% in the poor mathematical communication skills category, in cycle I meeting II there were 11 students who achieved mastery, which is 60% in the poor mathematical communication skills category, in cycle II meeting I there were 14 students who achieved mastery, which is 70% in the good mathematical communication skills category, and then in cycle II meeting II there were 18 students who achieved mastery, which is 90% in the very good mathematical communication skills category. Thus, it can be concluded that the application of the problem based learning model can improve students' mathematical communication in Mathematics learning in class IV of Muhammadiyah 028 Penyasawan Elementary School.